(untitled) (Research, Society and Development, 2025)
The aim of this study was to evaluate the seedling development of five dwarf cashew clones (CCP 76, BRS 226, BRS 189, BRS 265 and BRS 275) under the climatic conditions of the Cerrado in Uberlândia, Minas Gerais (MG), in order to identify genetic materials with greater adaptation potential and vegetative vigor. The experiment was carried out in a nursery between July 2022 and June 2023, in a randomized block design with five treatments and five replications. Plant height and stem collar diameter were measured monthly, and data were analyzed using analysis of variance and Tukey’s test at 5% probability. Significant differences among clones were observed only for height. Clone BRS 189 showed the greatest mean growth (27.66 cm), followed by BRS 265 (27.26 cm), while the hybrid BRS 275 presented the lowest value (22.12 cm). No significant differences were detected for collar diameter, with an overall mean increment of approximately 5 mm. The height-to-diameter ratio ranged from 1.84 (BRS 275) to 2.78 (CCP 76), indicating suitable morphological balance among seedlings. The results indicate that all clones showed adequate performance for commercial seedling production under Cerrado nursery conditions, with BRS 189 and BRS 265 standing out for their greater initial vigor. Field evaluation is recommended to determine whether the early growth differences persist and translate into greater productivity and better long-term adaptation.